A composite power generation yarn based on triboelectric-piezoelectric synergy and a preparation method thereof
Composite power-generating yarns with ZnO/PVA binder layer, modified BaTiO3/PVDF conjugate electrospun layer, and modified TiO2/PTFE/PDMS coating were prepared by conjugate electrospinning technology. This solved the problems of mechanical energy harvesting efficiency and material compatibility of existing yarns, and achieved high-efficiency charge output and stability, making it suitable for self-powered fabrics.
Patent Information
- Application Number
- CN202610589928.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-30
- Publication Date
- 2026-08-04
- Estimated Expiration
- 2046-04-30
AI Technical Summary
Existing yarn structures have limitations in mechanical energy harvesting efficiency, making it difficult to fully capture multi-mode, wide-frequency mechanical energy during human movement. Furthermore, material selection suffers from poor compatibility, uneven dispersion, and weak interfacial bonding, affecting charge output efficiency and textile processing adaptability.
A composite power-generating yarn consisting of a ZnO/PVA binder layer, a modified BaTiO3/PVDF conjugate electrospun layer, and a modified TiO2/PTFE/PDMS coating was prepared using conjugate electrospinning technology. Through the synergistic effect of triboelectric and piezoelectric effects, a piezoelectric functional layer and a triboelectric functional layer were formed, achieving efficient collection and conversion of mechanical energy.
It significantly improves charge output efficiency and stability, and the yarn can efficiently collect and convert mechanical energy during human movement. It also has flexibility and textile processing adaptability, making it suitable for fabric structures in the field of self-powered power supply.
Smart Images

Figure CN122105715B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of piezoelectric fabric technology, specifically to a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect and its preparation method. Background Technology
[0002] With the rapid development of wearable electronic devices, higher demands are being placed on the flexibility, lightweighting, and sustainability of their power supply systems. Traditional rigid batteries are insufficient to meet the comfort and integration requirements of flexible wearables. Therefore, energy harvesting technology, which collects mechanical energy from the human body's movement environment and converts it into electrical energy, has become a research hotspot. Among them, triboelectric nanogenerators (TENGs) and piezoelectric nanogenerators (PENGs) have shown broad application prospects in the field of flexible wearable energy devices due to their advantages such as simple structure, wide range of material choices, and high energy conversion efficiency. Currently, power generation devices based on fiber or yarn structures are considered an effective way to realize electronic textiles (E-textiles) due to their good weaving compatibility, breathability, and wearing comfort. In existing technologies, researchers have attempted to load triboelectric or piezoelectric materials onto the surface of conductive fibers through coating, impregnation, or electrospinning to prepare yarns with a single power generation function. For example, fiber-based triboelectric nanogenerators can be constructed by impregnating conductive yarns with triboelectric materials such as polydimethylsiloxane (PDMS) or polytetrafluoroethylene (PTFE); or fiber-based piezoelectric nanogenerators can be prepared by coating the yarn surface with piezoelectric materials such as polyvinylidene fluoride (PVDF). However, such single-mechanism power-generating yarns have limitations in mechanical energy harvesting efficiency, making it difficult to fully capture the multi-mode, wide-frequency mechanical energy generated by human movement. To improve energy harvesting efficiency, researchers have attempted to combine the triboelectric and piezoelectric effects to design composite structure devices. Existing composite structures mostly employ laminated or thin-film stacked designs, fabricating the triboelectric and piezoelectric layers separately and then combining them. Although this achieves the superposition of the two effects, it suffers from problems such as weak interlayer bonding, poor overall device flexibility, large thickness, and difficulty in achieving integrated integration at the yarn scale. Furthermore, such structures are prone to delamination or performance degradation during textile processing, limiting their practical application in fabrics. Regarding material selection, while piezoelectric materials such as barium titanate (BaTiO3) and zinc oxide (ZnO) possess high piezoelectric coefficients, they suffer from poor compatibility with polymer matrices, uneven dispersion, and easy agglomeration, affecting the stable performance of piezoelectric properties. Triboelectric materials such as PDMS and PTFE exhibit excellent tribone negativity, but their low dielectric constants necessitate further improvement in charge storage and retention capabilities. Furthermore, existing technologies lack systematic consideration of the interface design between piezoelectric and triboelectric layers, as well as charge transport and recombination loss suppression, making it difficult to achieve a true synergistic enhancement of the two effects. Therefore, how to effectively synergize the piezoelectric and triboelectric effects at the yarn scale, improve charge output efficiency, and simultaneously ensure material structural stability and textile processing adaptability is a pressing technical problem to be solved. Summary of the Invention
[0003] The purpose of this invention is to overcome the shortcomings of the prior art and provide a composite power-generating yarn based on the synergistic effect of triboelectric and piezoelectricity, which has high charge output efficiency and stability.
[0004] This invention also provides a method for preparing composite power-generating yarn based on the synergistic effect of triboelectric and piezoelectricity. Based on conjugate electrospinning technology, the method utilizes the piezoelectric effect of the ZnO / PVA binder layer and the modified BaTiO3 / PVDF conjugate electrospinning layer, as well as the triboelectric effect of the co-modified BaTiO3 / PVDF conjugate electrospinning layer and the modified TiO2 / PTFE / PDMS coating, to achieve a yarn electrical output performance that is significantly better than that of a single working mechanism, thereby realizing the efficient collection and conversion of mechanical energy.
[0005] The technical problem solved by this invention is achieved through the following technical solution: A composite power-generating yarn based on triboelectric-piezoelectric synergy includes an electrode core layer and a triboelectric layer wrapping the electrode core layer; The electrode core layer is made of pure copper wire; the friction layer includes a ZnO / PVA adhesive layer, a modified BaTiO3 / PVDF conjugate electrospun layer, and a modified TiO2 / PTFE / PDMS coating; the ZnO / PVA adhesive layer and the modified BaTiO3 / PVDF conjugate electrospun layer form a piezoelectric functional layer, which generates piezoelectric charges when in contact with the fabric; the modified BaTiO3 / PVDF conjugate electrospun layer and the modified TiO2 / PTFE / PDMS coating form a triboelectric functional layer, which generates triboelectric charges through contact separation; through the synergistic effect of triboelectric and piezoelectric effects, mechanical energy is collected and converted.
[0006] A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution; (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of modified BaTiO3 powder; (2) Preparation of modified BaTiO3 / PVDF solution; (3) The modified BaTiO3 / PVDF solution was collected by conjugate electrospinning technology to obtain modified BaTiO3 / PVDF nanofibers; (4) Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer; Step 3: Prepare yarn containing a modified TiO2 / PTFE / PDMS coating: (1) Preparation of modified TiO2 powder; (2) Preparation of PDMS solution; (3) Preparation of modified TiO2 / PTFE / PDMS solution; (4) Prepare yarn containing modified TiO2 / PTFE / PDMS coating. Preparation complete.
[0007] Furthermore, the ZnO / PVA adhesive layer of the composite power-generating yarn based on triboelectric-piezoelectric synergy is made of ZnO and PVA; the modified BaTiO3 / PVDF conjugate electrospinning layer is made of modified BaTiO3 and PVDF; and the modified TiO2 / PTFE / PDMS coating is made of modified TiO2, PTFE, and PDMS.
[0008] Further, the preparation of the ZnO / PVA solution in step 1 includes the following steps: A PVA solution was prepared by dissolving 9 wt% PVA particles in deionized water and stirring at 85°C until dissolved. 5 wt% ZnO particles were added to a PVA solution, stirred at 60°C for 1 h, and sonicated for 30 min to prepare a ZnO / PVA solution.
[0009] Further, step 2, preparing modified BaTiO3 powder, includes the following steps: Weigh a certain amount of BaTiO3, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare BaTiO3 slurry; Weigh out 1-2% of silane coupling agent KH550 relative to BaTiO3 by mass and pour it into BaTiO3 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified BaTiO3 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. The preparation of modified BaTiO3 / PVDF solution includes the following steps: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. Add 5-10 wt% of modified BaTiO3 powder to PVDF solution, stir at 60℃ for 3 h, and sonicate for 1 h to prepare modified BaTiO3 / PVDF solution; Modified BaTiO3 / PVDF nanofibers were collected from the modified BaTiO3 / PVDF solution using conjugate electrospinning technology, including the following steps: The modified BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the modified BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 5~15kV, solution flow rate 0.2~0.5mL / h, and distance from needle tip to collector 12~18cm. The preparation of yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer includes the following steps: The yarn containing the ZnO / PVA binder layer prepared in step 1 is wrapped with modified BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours. A modified BaTiO3 / PVDF conjugate electrospinning layer is formed on the yarn containing the ZnO / PVA binder layer, thus preparing the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer.
[0010] Further, step 3, preparing modified TiO2 powder, includes the following steps: Weigh a certain amount of TiO2, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare TiO2 slurry; Weigh out 1-2% of silane coupling agent KH550 relative to TiO2 mass percentage and pour it into TiO2 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified TiO2 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. The preparation of PDMS solution includes the following steps: The ratio of PDMS main agent to curing agent is 10:1, and the concentration is 20~30wt%. PDMS is added to n-heptane solvent and stirred for 30~60 minutes to prepare PDMS solution. The preparation of the modified TiO2 / PTFE / PDMS solution includes the following steps: 0.1-5 wt% modified TiO2 powder and 0.1-5 wt% PTFE were added to PDMS solution, stirred for 2 h, and then sonicated for 1 h to prepare modified TiO2 / PTFE / PDMS solution. The preparation of yarn containing a modified TiO2 / PTFE / PDMS coating includes the following steps: The yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer prepared in step 2 is immersed in a modified TiO2 / PTFE / PDMS solution for 20 min and then dried in an oven at 80°C. A modified TiO2 / PTFE / PDMS coating is formed on the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer, thus preparing yarn with a modified TiO2 / PTFE / PDMS coating.
[0011] The advantages and positive effects of this invention are: 1. This invention relates to a composite power-generating yarn based on the synergistic effect of triboelectric and piezoelectricity, comprising an electrode core layer and a friction layer encasing the electrode core layer; the electrode core layer is made of pure copper wire, which can reduce production costs and effectively improve electrical output performance; the friction layer comprises a ZnO / PVA adhesive layer, a modified BaTiO3 / PVDF conjugate electrospinning layer, and a modified TiO2 / PTFE / PDMS coating, exhibiting high charge output efficiency and stability.
[0012] 2. This invention relates to a method for preparing composite power-generating yarn based on the synergistic effect of triboelectric and piezoelectricity. A ZnO / PVA adhesive layer and a modified BaTiO3 / PVDF conjugate electrospinning layer form a piezoelectric functional layer, which generates piezoelectric charges when in contact with the fabric. A modified BaTiO3 / PVDF conjugate electrospinning layer and a modified TiO2 / PTFE / PDMS coating form a triboelectric functional layer, which generates triboelectric charges through contact separation. Through the synergistic effect of triboelectric and piezoelectricity, mechanical energy is collected and converted.
[0013] 3. The composite power-generating yarn prepared by this invention, based on the synergistic effect of triboelectricity and piezoelectricity, integrates the synergistic effect of triboelectricity and piezoelectricity to form a high-dielectric functional triboelectric layer outside the electrode material. This triboelectric layer can not only efficiently capture mechanical energy from the environment and convert it into triboelectric energy through mechanical friction with the contact interface, but also generate additional piezoelectric potential during deformation under stress by means of the piezoelectric effect. The superposition of the two effects significantly improves the energy conversion efficiency and output stability. A 5cm long yarn in single-electrode mode (frequency 3Hz, pressure 25N) outputs a voltage of 23.5V. When the human body moves, on the one hand, the two friction materials generate triboelectricity due to continuous contact and separation; on the other hand, the spacer material with piezoelectric properties excites the piezoelectric effect under the action of motion deformation. The synergistic effect of the two significantly improves the electrical signal output efficiency; the generated electrical signal can be stably output through the intermediate electrode material.
[0014] 4. The composite power-generating yarn based on the synergistic effect of triboelectricity and piezoelectricity prepared by this invention can be applied to the field of self-powered energy. Since the power-generating yarn itself is a yarn raw material, it has processing compatibility with various fabric structures, allowing for continuous output in ordinary woven, knitted, or braided structures without additional interlayer combinations. Its electrical properties are improved compared to traditional laminated TENG fabrics, and its flexibility, fatigue resistance, and washability are comparable to conventional clothing yarns, combining wearing comfort and multifunctionality, effectively increasing product added value. This yarn can be blended with conventional fibers such as cotton and polyester for use in knitwear and other garments, such as elbows and knees, or in textiles, providing a scalable in-situ energy harvesting pathway for apparel, home textiles, and industrial textiles. Attached Figure Description
[0015] Figure 1 This is a flowchart of the preparation method of composite power-generating yarn based on triboelectric-piezoelectric synergistic effect in Embodiment 4 of the present invention; Figure 2 The diagram shows the electrical output performance of the composite power-generating yarn based on the synergistic effect of triboelectricity and piezoelectricity in Embodiments 1-2 of the present invention. Figure 3 The diagram shows the electrical output performance of the composite power-generating yarn based on the synergistic effect of triboelectricity and piezoelectricity in Embodiments 3-4 of the present invention. Figure 4 The diagram shows the electrical output performance of the composite power-generating yarn based on the synergistic effect of triboelectricity and piezoelectricity in Embodiments 4-6 of the present invention. Figure 5 This is Example 4 of the present invention, which describes the self-powered application of a composite power generation system based on the synergistic effect of triboelectric and piezoelectricity using three strands of yarn. Detailed Implementation
[0016] The present invention will be further described in detail below through specific embodiments. The following embodiments are merely descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.
[0017] The present invention relates to a composite power-generating yarn based on the synergistic effect of triboelectric and piezoelectricity, comprising an electrode core layer and a triboelectric layer encapsulating the electrode core layer.
[0018] The electrode core layer is made of pure copper wire; the friction layer includes a ZnO / PVA adhesive layer, a modified BaTiO3 / PVDF conjugate electrospun layer, and a modified TiO2 / PTFE / PDMS coating; the ZnO / PVA adhesive layer and the modified BaTiO3 / PVDF conjugate electrospun layer form a piezoelectric functional layer, which generates piezoelectric charges when in contact with the fabric; the modified BaTiO3 / PVDF conjugate electrospun layer and the modified TiO2 / PTFE / PDMS coating form a triboelectric functional layer, which generates triboelectric charges through contact separation; through the synergistic effect of triboelectric and piezoelectric effects, mechanical energy is collected and converted.
[0019] The materials for the ZnO / PVA adhesive layer include zinc oxide (ZnO) and polyvinyl alcohol (PVA); the materials for the modified BaTiO3 / PVDF conjugated electrospinning layer include modified barium titanate (BaTiO3) and polyvinylidene fluoride (PVDF); and the materials for the modified TiO2 / PTFE / PDMS coating include modified titanium dioxide (TiO2), polytetrafluoroethylene (PTFE), and polydimethylsiloxane (PDMS).
[0020] Example 1 A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare PVDF solution: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. Step 2: Collect PVDF nanofibers from the PVDF solution using conjugate electrospinning technology. The PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the PVDF nanofibers. The electrospinning parameters were: applied voltage 5kV, solution flow rate 0.45mL / h, and distance from the needle tip to the collector 15cm. Step 3: Prepare the yarn. Pure copper yarn was wrapped with nanofibers and dried in a vacuum oven at 60°C for 12 hours to prepare yarn.
[0021] The electrical output performance of the composite power-generating yarn based on triboelectric-piezoelectric synergy prepared in Example 1 is as follows: Figure 2 As shown by the curve on the left, the electrical output performance is significantly lower than that of Example 2.
[0022] Example 2 A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution: A PVA solution was prepared by dissolving 9 wt% PVA particles in deionized water and stirring at 85°C until dissolved. 5 wt% ZnO particles were added to a PVA solution, stirred at 60°C for 1 h, and sonicated for 30 min to prepare a ZnO / PVA solution. (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of BaTiO3 / PVDF solution: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. BaTiO3 (8 wt%) was added to a PVDF solution, stirred at 60°C for 3 h, and sonicated for 1 h to prepare a BaTiO3 / PVDF solution. (2) BaTiO3 / PVDF nanofibers were collected from the BaTiO3 / PVDF solution using conjugate electrospinning: The BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 15kV, solution flow rate 0.35mL / h, and distance from needle tip to collector 18cm. (3) Preparation of yarn containing a BaTiO3 / PVDF conjugate electrospinning layer: The yarn containing the ZnO / PVA adhesive layer prepared in step 1 is wrapped with BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours to form a BaTiO3 / PVDF conjugate electrospinning layer on the yarn containing the ZnO / PVA adhesive layer, thus preparing the yarn containing the BaTiO3 / PVDF conjugate electrospinning layer. Step 3: Prepare yarn with PDMS coating: (1) Preparation of PDMS solution: The ratio of PDMS main agent to curing agent is 10:1, and the concentration is 30wt%. PDMS is added to n-heptane solvent and stirred for 45 minutes to prepare PDMS solution. (2) Preparation of yarn with PDMS coating: The yarn containing the BaTiO3 / PVDF conjugate electrospinning layer prepared in step 2 was immersed in PDMS solution for 20 minutes and then dried in an oven at 80°C. A PDMS coating was formed on the yarn containing the BaTiO3 / PVDF conjugate electrospinning layer, and the preparation of the yarn containing the PDMS coating was completed.
[0023] Example 2 prepared a composite power-generating yarn based on triboelectric-piezoelectric synergy, in which the BaTiO3 content was 8wt% and the electrical output performance was the highest. Adding a ZnO / PVA binder layer and a BaTiO3 / PVDF conjugate electrospinning layer further improved the electrical output performance. A 5cm long yarn from this example achieved an output voltage of 7.2V in single-electrode mode (3Hz frequency, 25N pressure). Figure 2 As shown by the curve on the right.
[0024] Example 3 A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution: A PVA solution was prepared by dissolving 9 wt% PVA particles in deionized water and stirring at 85°C until dissolved. 5 wt% ZnO particles were added to a PVA solution, stirred at 60°C for 1 h, and sonicated for 30 min to prepare a ZnO / PVA solution. (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of modified BaTiO3 powder: Weigh a certain amount of BaTiO3, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare BaTiO3 slurry; Weigh 1.5% of silane coupling agent KH550 relative to BaTiO3 by mass and pour it into BaTiO3 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified BaTiO3 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of modified BaTiO3 / PVDF solution: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. 8 wt% of modified BaTiO3 powder was added to PVDF solution, stirred at 60℃ for 3 h, and sonicated for 1 h to prepare modified BaTiO3 / PVDF solution. (3) The modified BaTiO3 / PVDF solution was collected using conjugate electrospinning technology to obtain modified BaTiO3 / PVDF nanofibers: The modified BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the modified BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 7.5kV, solution flow rate 0.45mL / h, and distance from needle tip to collector 15cm. (4) Preparation of yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: The yarn containing the ZnO / PVA binder layer prepared in step 1 is wrapped with modified BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours. A modified BaTiO3 / PVDF conjugate electrospinning layer is formed on the yarn containing the ZnO / PVA binder layer, and the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer is prepared. The preparation is complete.
[0025] The electrical output performance of the composite power-generating yarn based on triboelectric-piezoelectric synergy prepared in Example 3 is as follows: Figure 3 As shown by the curve on the left, its electrical output performance is significantly lower than that of Example 4.
[0026] Example 4 like Figure 1 As shown, a method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution: A PVA solution was prepared by dissolving 9 wt% PVA particles in deionized water and stirring at 85°C until dissolved. 5 wt% ZnO particles were added to a PVA solution, stirred at 60°C for 1 h, and sonicated for 30 min to prepare a ZnO / PVA solution. (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of modified BaTiO3 powder: Weigh a certain amount of BaTiO3, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare BaTiO3 slurry; Weigh 1.5% of silane coupling agent KH550 relative to BaTiO3 by mass and pour it into BaTiO3 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified BaTiO3 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of modified BaTiO3 / PVDF solution: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. 8 wt% of modified BaTiO3 powder was added to PVDF solution, stirred at 60℃ for 3 h, and sonicated for 1 h to prepare modified BaTiO3 / PVDF solution. (3) The modified BaTiO3 / PVDF solution was collected using conjugate electrospinning technology to obtain modified BaTiO3 / PVDF nanofibers: The modified BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the modified BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 7.5kV, solution flow rate 0.45mL / h, and distance from needle tip to collector 15cm. (4) Preparation of yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: The yarn containing the ZnO / PVA adhesive layer prepared in step 1 is wrapped with modified BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours. A modified BaTiO3 / PVDF conjugate electrospinning layer is formed on the yarn containing the ZnO / PVA adhesive layer, thus preparing the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer. Step 3: Prepare yarn containing a modified TiO2 / PTFE / PDMS coating: (1) Preparation of modified TiO2 powder: Weigh a certain amount of TiO2, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare TiO2 slurry; Weigh 1.5% of silane coupling agent KH550 relative to TiO2 mass percentage and pour it into TiO2 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified TiO2 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of PDMS solution: The ratio of PDMS main agent to curing agent is 10:1, and the concentration is 20wt%. PDMS is added to n-heptane solvent and stirred for 30~60 minutes to prepare PDMS solution. (3) Preparation of modified TiO2 / PTFE / PDMS solution: 2 wt% modified TiO2 powder and 2 wt% PTFE were added to PDMS solution, stirred for 2 h, and then sonicated for 1 h to prepare modified TiO2 / PTFE / PDMS solution. (4) Preparation of yarn containing modified TiO2 / PTFE / PDMS coating: The yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer prepared in step 2 is immersed in a modified TiO2 / PTFE / PDMS solution for 20 minutes and then dried in an oven at 80°C. A modified TiO2 / PTFE / PDMS coating is formed on the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer, and the preparation of yarn containing the modified TiO2 / PTFE / PDMS coating is completed.
[0027] The composite power-generating yarn prepared in Example 4, based on the synergistic effect of triboelectricity and piezoelectricity, is a three-strand yarn, and its electrical output performance is as follows: Figure 3 The curve on the right side of the middle section, Figure 4 As shown in the middle curve, the electrical output performance of the yarn with modified BaTiO3 and modified TiO2 is significantly improved. A 5cm length of this yarn, in single-electrode mode (frequency 3Hz, pressure 25N), can achieve an output voltage of 23.5V, sufficient to power a calculator. Figure 5 As shown.
[0028] The composite power-generating yarn based on the synergistic effect of triboelectricity and piezoelectricity exhibits superior electrical output performance through the combined action of these two effects. Specifically, a ZnO / PVA binder layer and a modified BaTiO3 / PVDF conjugate electrospinning layer form a piezoelectric functional layer, generating piezoelectric charges upon contact with the fabric; a modified BaTiO3 / PVDF conjugate electrospinning layer and a modified TiO2 / PTFE / PDMS coating form a triboelectric functional layer, generating triboelectric charges upon contact and separation. The core of this synergy lies in the fact that, based on triboelectricity and electrostatic induction, and in conjunction with the piezoelectric effect, the overall output performance of this yarn is significantly superior to that of a single working mechanism, thus achieving highly efficient collection and conversion of mechanical energy.
[0029] Example 5 A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution: A PVA solution was prepared by dissolving 9 wt% PVA particles in deionized water and stirring at 85°C until dissolved. 5 wt% ZnO particles were added to a PVA solution, stirred at 60°C for 1 h, and sonicated for 30 min to prepare a ZnO / PVA solution. (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of modified BaTiO3 powder: Weigh a certain amount of BaTiO3, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare BaTiO3 slurry; Weigh 1.5% of silane coupling agent KH550 relative to BaTiO3 by mass and pour it into BaTiO3 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified BaTiO3 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of modified BaTiO3 / PVDF solution: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. 8 wt% of modified BaTiO3 powder was added to PVDF solution, stirred at 60℃ for 3 h, and sonicated for 1 h to prepare modified BaTiO3 / PVDF solution. (3) The modified BaTiO3 / PVDF solution was collected using conjugate electrospinning technology to obtain modified BaTiO3 / PVDF nanofibers: The modified BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the modified BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 6.5 kV, solution flow rate 0.5 mL / h, and distance from needle tip to collector 16 cm. (4) Preparation of yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: The yarn containing the ZnO / PVA adhesive layer prepared in step 1 is wrapped with modified BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours. A modified BaTiO3 / PVDF conjugate electrospinning layer is formed on the yarn containing the ZnO / PVA adhesive layer, thus preparing the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer. Step 3: Prepare yarn containing a modified TiO2 / PTFE / PDMS coating: (1) Preparation of modified TiO2 powder: Weigh a certain amount of TiO2, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare TiO2 slurry; Weigh out 1% of the silane coupling agent KH550 relative to the mass percentage of TiO2 and pour it into the TiO2 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified TiO2 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of PDMS solution: The ratio of PDMS main agent to curing agent is 10:1, and the concentration is 20wt%. PDMS is added to n-heptane solvent and stirred for 30~60 minutes to prepare PDMS solution. (3) Preparation of modified TiO2 / PTFE / PDMS solution: 2 wt% modified TiO2 powder and 2 wt% PTFE were added to PDMS solution, stirred for 2 h, and then sonicated for 1 h to prepare modified TiO2 / PTFE / PDMS solution. (4) Preparation of yarn containing modified TiO2 / PTFE / PDMS coating: The yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer prepared in step 2 is immersed in a modified TiO2 / PTFE / PDMS solution for 20 minutes and then dried in an oven at 80°C. A modified TiO2 / PTFE / PDMS coating is formed on the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer, and the preparation of yarn containing the modified TiO2 / PTFE / PDMS coating is completed.
[0030] The electrical output performance of the composite power-generating yarn based on triboelectric-piezoelectric synergy prepared in Example 5 is as follows: Figure 4 As shown by the curve on the left, the electrical output performance is significantly lower than that of Example 4.
[0031] Example 6 A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution: A PVA solution was prepared by dissolving 9 wt% PVA particles in deionized water and stirring at 85°C until dissolved. 5 wt% ZnO particles were added to a PVA solution, stirred at 60°C for 1 h, and sonicated for 30 min to prepare a ZnO / PVA solution. (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of modified BaTiO3 powder: Weigh a certain amount of BaTiO3, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare BaTiO3 slurry; Weigh 1.5% of silane coupling agent KH550 relative to BaTiO3 by mass and pour it into BaTiO3 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified BaTiO3 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of modified BaTiO3 / PVDF solution: A PVDF solution was prepared by dissolving 9 wt% PVDF particles in DMF solvent and stirring at 60°C until dissolved. 8 wt% of modified BaTiO3 powder was added to PVDF solution, stirred at 60℃ for 3 h, and sonicated for 1 h to prepare modified BaTiO3 / PVDF solution. (3) The modified BaTiO3 / PVDF solution was collected using conjugate electrospinning technology to obtain modified BaTiO3 / PVDF nanofibers: The modified BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the modified BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 8.5 kV, solution flow rate 0.4 mL / h, and distance from needle tip to collector 16 cm. (4) Preparation of yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: The yarn containing the ZnO / PVA adhesive layer prepared in step 1 is wrapped with modified BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours. A modified BaTiO3 / PVDF conjugate electrospinning layer is formed on the yarn containing the ZnO / PVA adhesive layer, thus preparing the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer. Step 3: Prepare yarn containing a modified TiO2 / PTFE / PDMS coating: (1) Preparation of modified TiO2 powder: Weigh a certain amount of TiO2, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare TiO2 slurry; Weigh out 2% of the silane coupling agent KH550 relative to the mass percentage of TiO2 and pour it into the TiO2 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified TiO2 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of PDMS solution: The ratio of PDMS main agent to curing agent is 10:1, and the concentration is 20wt%. PDMS is added to n-heptane solvent and stirred for 30~60 minutes to prepare PDMS solution. (3) Preparation of modified TiO2 / PTFE / PDMS solution: 2 wt% modified TiO2 powder and 2 wt% PTFE were added to PDMS solution, stirred for 2 h, and then sonicated for 1 h to prepare modified TiO2 / PTFE / PDMS solution. (4) Preparation of yarn containing modified TiO2 / PTFE / PDMS coating: The yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer prepared in step 2 is immersed in a modified TiO2 / PTFE / PDMS solution for 20 minutes and then dried in an oven at 80°C. A modified TiO2 / PTFE / PDMS coating is formed on the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer, and the preparation of yarn containing the modified TiO2 / PTFE / PDMS coating is completed.
[0032] The electrical output performance of the composite power-generating yarn based on triboelectric-piezoelectric synergy prepared in Example 6 is as follows: Figure 4 As shown by the curve on the right, the electrical output performance is significantly lower than that of Example 4.
[0033] This preparation method produces yarn with a composite structure, achieving an intrinsic synergy between triboelectric and piezoelectric effects at the yarn scale, enabling efficient harvesting and conversion of mechanical energy. A ZnO / PVA binder layer and a modified BaTiO3 / PVDF conjugate electrospun layer form a piezoelectric functional layer. Under deformations such as compression and bending transmitted from the fabric layer, the ZnO and BaTiO3 piezoelectric materials undergo crystal structure polarization, generating piezoelectric charges. A modified BaTiO3 / PVDF conjugate electrospun layer and a modified TiO2 / PTFE / PDMS coating form a triboelectric functional layer, generating triboelectric charges through contact separation.
[0034] The synergistic effect of triboelectricity and piezoelectricity in yarn: I. Piezoelectric Effect: The ZnO / PVA binder layer and the modified BaTiO3 / PVDF conjugate electrospun layer form a piezoelectric functional layer. When subjected to deformations such as compression and bending transmitted from the fabric layer, ZnO and the modified BaTiO3 piezoelectric material undergo crystal structure polarization, generating piezoelectric charges. The piezoelectric polarization of ZnO can induce free charges on the surface of the copper wire electrode, while the piezoelectric polarization of the modified BaTiO3 / PVDF forms a potential difference at the fiber interface. The two piezoelectric signals are output independently and superimposed.
[0035] II. Triboelectric Effect: Accompanied by the contact-separation deformation of the yarn structure, charge transfer occurs between the modified TiO2 / PTFE / PDMS coating and the nylon fabric due to the difference in electron affinity. The modified BaTiO3 / PVDF and modified TiO2 / PTFE / PDMS capture electrons and become negatively charged, while the nylon fabric loses electrons and becomes positively charged. During the contact-separation process, the repeated transfer and accumulation of charge form an alternating current, generating triboelectric output.
[0036] III. Synergistic Coupling Effect of Piezoelectricity and Triboelectricity: The piezoelectric effect can regulate the charge distribution on the yarn surface, improve the charge separation efficiency of triboelectric materials, reduce charge consumption, and thus enhance triboelectric output; the surface charge accumulated by the triboelectric effect will form an additional electric field, further promoting the lattice polarization of the piezoelectric material, improving the piezoelectric coefficient and electromechanical conversion efficiency, and strengthening the piezoelectric output.
[0037] Ultimately, the synergistic effect of the two makes the electrical output performance of this yarn far superior to that of a single piezoelectric or triboelectric nano-powered yarn, achieving efficient capture and conversion of mechanical energy.
[0038] PVA is used as a carrier for ZnO. The PVA molecular chain is rich in hydroxyl groups (-OH), which makes it highly susceptible to forming intramolecular and intermolecular hydrogen bonds. These hydrogen bond networks, along with the amorphous regions of PVA, can form numerous "charge traps." When triboelectric charges or piezoelectric charge carriers pass through these traps, they are easily captured, reducing charge consumption and increasing charge storage density and retention time.
[0039] PVDF is a strongly polar polymer, and the electronegativity difference of the CF bonds in its molecular chain results in a large dipole moment. In particular, its β phase, with dipoles aligned along the chain axis, exhibits excellent piezoelectricity and strong triboelectricity. BaTiO3 is a typical ferroelectric material containing spontaneously polarized electric dipoles. BaTiO3 can effectively induce PVDF to form a high content of electroactive β phase, which is crucial for generating and stabilizing charges. A high β phase content directly affects the stronger charge generation and storage capacity of PVDF.
[0040] Conjugate electrospinning technology can fabricate nanofiber structures with high specific surface area and high porosity. This structure can significantly increase the effective contact area of the friction interface, allowing more surface charge to be generated during friction. Under the high-voltage electric field and mechanical stretching of electrospinning, these domains align (polarize) along the direction of the electric field, forming a permanent polarized electric field within the material. This built-in electric field acts like a pre-stored charge reservoir, driving more electron transfer during contact and friction with PDMS, thereby significantly increasing the surface charge density.
[0041] TiO2 has a high dielectric constant, which can improve the overall dielectric properties of the composite coating, reduce leakage current, and provide dielectric support for charge accumulation for both effects. In addition, the high specific surface area of TiO2 can increase the internal interface of the coating and enhance the polarization effect.
[0042] PTFE is the strongest triboelectric negative material. It can easily capture electrons during contact separation, which greatly increases the charge density of the triboelectric interface. At the same time, its low charge recombination rate and high charge storage stability can serve as a long-term charge trapping layer to capture and fix the charges generated by triboelectricity and piezoelectricity, and inhibit the rapid loss of charge. The low surface energy of PTFE can also optimize the hydrophobicity of the coating surface and reduce the loss of surface charge due to environmental humidity.
[0043] PDMS is a strongly negatively charged material, and its surface can be further functionalized to control charge behavior; PDMS protects the internal structure and ensures durability; the hydrophobicity of PDMS helps maintain electrical properties in humid environments.
[0044] Although embodiments and drawings of the present invention have been disclosed for illustrative purposes, those skilled in the art will understand that various substitutions, variations and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A method for preparing a composite power-generating yarn based on triboelectric-piezoelectric synergistic effect, characterized in that: Its preparation method includes the following steps: Step 1: Prepare yarn containing a ZnO / PVA adhesive layer: (1) Preparation of ZnO / PVA solution; (2) After immersing pure copper wire in ZnO / PVA solution for 30 min, dry it in an oven at 60°C to form a ZnO / PVA adhesive layer on the pure copper wire, thus preparing yarn containing a ZnO / PVA adhesive layer. Step 2: Prepare yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer: (1) Preparation of modified BaTiO3 powder, including the following steps: Weigh a certain amount of BaTiO3, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare BaTiO3 slurry; Weigh out 1-2% of silane coupling agent KH550 relative to BaTiO3 by mass and pour it into BaTiO3 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified BaTiO3 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of modified BaTiO3 / PVDF solution, including the following steps: PVDF particles were dissolved in DMF solvent and stirred at 60°C until dissolved to prepare a PVDF solution. The mass percentage of PVDF particles in the solution was 9%. Modified BaTiO3 powder was added to PVDF solution, stirred at 60℃ for 3 h, and sonicated for 1 h to prepare modified BaTiO3 / PVDF solution. The mass percentage of modified BaTiO3 powder in the solution was 5~10%. (3) Collecting modified BaTiO3 / PVDF nanofibers from the modified BaTiO3 / PVDF solution using conjugate electrospinning technology, including the following steps: The modified BaTiO3 / PVDF solution was transferred to a plastic syringe, and electrospinning was performed using a No. 21 needle to collect the modified BaTiO3 / PVDF nanofibers. The electrospinning parameters were: applied voltage 5~15kV, solution flow rate 0.2~0.5mL / h, and distance from needle tip to collector 12~18cm. (4) Preparing yarn containing a modified BaTiO3 / PVDF conjugate electrospinning layer, including the following steps: The yarn containing the ZnO / PVA adhesive layer prepared in step 1 is wrapped with modified BaTiO3 / PVDF nanofibers and dried in a vacuum oven at 60°C for 12 hours. A modified BaTiO3 / PVDF conjugate electrospinning layer is formed on the yarn containing the ZnO / PVA adhesive layer, thus preparing the yarn containing the modified BaTiO3 / PVDF conjugate electrospinning layer. Step 3: Prepare yarn containing a modified TiO2 / PTFE / PDMS coating: (1) Preparation of modified TiO2 powder, including the following steps: Weigh a certain amount of TiO2, add an appropriate amount of anhydrous ethanol, stir for 30 min, and prepare TiO2 slurry; Weigh out 1-2% of silane coupling agent KH550 relative to TiO2 mass percentage and pour it into TiO2 slurry. Disperse it evenly by ultrasonic stirring and pour it into a three-necked flask. Stir it with a stirrer in an ultrasonic water bath for 3 hours. Then, centrifuge and wash it multiple times to prepare modified TiO2 powder. Place it in a vacuum drying oven, dry it under vacuum, and store it in a desiccator for later use. (2) Preparation of PDMS solution, including the following steps: The ratio of PDMS main agent to curing agent is 10:1, and the concentration is 20~30wt%. PDMS is added to n-heptane solvent and stirred for 30~60 minutes to prepare PDMS solution. (3) Preparation of modified TiO2 / PTFE / PDMS solution, including the following steps: Modified TiO2 powder and PTFE were added to a PDMS solution, stirred for 2 hours, and then sonicated for 1 hour to prepare a modified TiO2 / PTFE / PDMS solution. The mass percentages of modified TiO2 powder and PTFE in the solution were both 0.1% to 5%. (4) Preparing yarn containing a modified TiO2 / PTFE / PDMS coating, including the following steps: The yarn containing the modified BaTiO3 / PVDF conjugate electrospun layer prepared in step 2 was immersed in a modified TiO2 / PTFE / PDMS solution for 20 min, and then dried in an oven at 80℃. A modified TiO2 / PTFE / PDMS coating was formed on the yarn containing the modified BaTiO3 / PVDF conjugate electrospun layer, thus preparing yarn with a modified TiO2 / PTFE / PDMS coating; preparation complete. Its composite power-generating yarn includes an electrode core layer and a friction layer that wraps around the electrode core layer; The electrode core layer is made of pure copper wire; the friction layer includes a ZnO / PVA adhesive layer, a modified BaTiO3 / PVDF conjugate electrospun layer, and a modified TiO2 / PTFE / PDMS coating; the ZnO / PVA adhesive layer and the modified BaTiO3 / PVDF conjugate electrospun layer form a piezoelectric functional layer, which generates piezoelectric charges when in contact with the fabric; the modified BaTiO3 / PVDF conjugate electrospun layer and the modified TiO2 / PTFE / PDMS coating form a triboelectric functional layer, which generates triboelectric charges through contact separation; through the synergistic effect of triboelectric and piezoelectric effects, mechanical energy is collected and converted.
2. The method for preparing composite power-generating yarn based on triboelectric-piezoelectric synergistic effect according to claim 1, characterized in that: The ZnO / PVA adhesive layer of the composite power-generating yarn based on triboelectric-piezoelectric synergy is made of ZnO and PVA; the modified BaTiO3 / PVDF conjugate electrospinning layer is made of modified BaTiO3 and PVDF; and the modified TiO2 / PTFE / PDMS coating is made of modified TiO2, PTFE, and PDMS.
3. The method for preparing composite power-generating yarn based on triboelectric-piezoelectric synergistic effect according to claim 1, characterized in that: The preparation of the ZnO / PVA solution in step 1 includes the following steps: PVA particles were dissolved in deionized water and stirred at 85°C until dissolved to prepare a PVA solution. The mass percentage of PVA particles in the solution was 9%. ZnO particles were added to a PVA solution, stirred at 60°C for 1 hour, and sonicated for 30 minutes to prepare a ZnO / PVA solution with a ZnO particle mass percentage of 5%.